Blockade of RAGE ameliorates elastase‐induced emphysema development and progression via RAGE‐DAMP signaling. Issue 5 (1st February 2017) - Lee, Hanbyeol; Park, Jeong-Ran; Kim, Woo Jin; Sundar, Isaac K.; Rahman, Irfan; Park, Sung-Min; Yang, Se-Ran
ABSTRACT: The receptor for advanced glycan end products (RAGE) has been identified as a susceptibility gene for chronic obstructive pulmonary disease (COPD) in genome‐wide association studies (GWASs). However, less is known about how RAGE is involved in the pathogenesis of COPD. To determine the molecular mechanism by which RAGE influences COPD in experimental COPD models, we investigated the efficacy of the RAGE‐specific antagonist FPS‐ZM1 administration in in vivo and in vitro COPD models. We injected elastase intratracheally and the RAGE antagonist FPS‐ZM1 in mice, and the infiltrated inflammatory cells and cytokines were assessed by ELISA. Cellular expression of RAGE was determined in protein, serum, and bronchoalveolar lavage fluid of mice and lungs and serum of human donors and patients with COPD. Downstream damage‐associated molecular pattern (DAMP) pathway activation in vivo and in vitro and in patients with COPD was assessed by immunofluorescence staining, Western blot analysis, and ELISA. The expression of membrane RAGE in initiating the inflammatory response and of soluble RAGE acting as a decoy were associated with up‐regulation of the DAMP‐related signaling pathway via Nrf2. FPS‐ZM1 administration significantly reversed emphysema in the lung of mice. Moreover, FPS‐ZM1 treatment significantly reduced lung inflammation in Nrf2 +/+, but not in Nrf2 ‒ / ‒ mice. Thus, our data indicate for the first time that RAGE inhibition has an essential protective role in COPD. Our observation of RAGE inhibition provided novel insight into its potential as a therapeutic target in emphysema/COPD.—Lee, H., Park, J.‐R., Kim, W. J., Sundar, I. K., Rahman, I., Park, S.‐M., Yang. S.‐R. Blockade of RAGE ameliorates elastase‐induced emphysema development and progression via RAGE‐DAMP signaling. FASEB J. 31, 2076–2089 (2017). www.fasebj.org